2019
DOI: 10.1055/s-0039-3402450
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of System End-User Support during Implementation of an Electronic Health Record Using the Model for Improvement Framework

Abstract: Background Electronic health record (EHR) system implementation is complex. Strong support for clinicians and other end-users during the initial phase of implementation requires dedicated resources and commitment to ensure a smooth transition, reduce frustration, and assist in adoption. Objectives Evaluate end-user support processes and personnel employed during the initial phase of EHR implementation at an academic medical center and identify facilitators of success, challenges, and lessons learned.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…The present study examined and analyzed the factors and indicated the most remarkable effectiveness of the HIS in improving the clinical staff performance occurred by accelerating paraclinical activities, the process of diagnosis and treatment, access to quality information, and medical research. The results of some other studies also confirmed the findings of the present study [11,30,31].…”
Section: Discussionsupporting
confidence: 93%
“…The present study examined and analyzed the factors and indicated the most remarkable effectiveness of the HIS in improving the clinical staff performance occurred by accelerating paraclinical activities, the process of diagnosis and treatment, access to quality information, and medical research. The results of some other studies also confirmed the findings of the present study [11,30,31].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we note the challenges of investigations in the EHR, a topic extensively discussed in the literature, 106,107 which might have influenced our results. The ETL process that converts the clinical data into the OMOP data tables is a dynamic process that improves over time, but is not completely error free.…”
Section: Discussionmentioning
confidence: 97%
“…This study emphasizes several other topics described in our interviews, including staff changes and organizational restructuring. Kiepek and Sengstack 27 also acknowledge the importance of on-site support for end-users during the transition but do not discuss the preparatory work to get to the actual implementation. Overall, our findings support claims from these studies but broaden the scope with respect to the variety in healthcare settings and resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…There can also be extreme difficulty for an organization to develop and maintain its own HIT systems, which often leads organizations away from keeping their homegrown systems, despite the benefits that they may bring. Kiepek and Sengstack 27 suggest some potential success indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation